2021
DOI: 10.1155/2021/6687291
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment 18F-FDG PET/CT Imaging Predicts the KRAS/NRAS/BRAF Gene Mutational Status in Colorectal Cancer

Abstract: Objective. To investigate the association between KRAS/NRAS/BRAF mutations and metabolic parameters of pretreatment 18F-FDG PET/CT in colorectal cancer (CRC). Methods. A total of 85 patients with CRC were included in the study. PET/CT was performed in all the patients before surgery. The histopathological examination and analysis of the gene mutational status of the primary tumor were conducted. The associations among clinical features, PET metabolic parameters, and the gene mutational status were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Mutant KRAS also upregulates expression of the GLUT1 glucose transporter, promoting glucose uptake by cells. Interestingly, several studies have demonstrated higher glucose accumulation in 18F-FDG PET/CT scans in CRCs with KRAS/NRAS/BRAF mutations [48]. The association between myosteatosis and serrated morphology suggests that serrated CRC patients might have an increased risk of myosteatosis, and we hypothesize that this may reflect higher glucose metabolism in serrated CRC.…”
Section: Discussionmentioning
confidence: 71%
“…Mutant KRAS also upregulates expression of the GLUT1 glucose transporter, promoting glucose uptake by cells. Interestingly, several studies have demonstrated higher glucose accumulation in 18F-FDG PET/CT scans in CRCs with KRAS/NRAS/BRAF mutations [48]. The association between myosteatosis and serrated morphology suggests that serrated CRC patients might have an increased risk of myosteatosis, and we hypothesize that this may reflect higher glucose metabolism in serrated CRC.…”
Section: Discussionmentioning
confidence: 71%
“…PET/CT is a systemic examination that can detect the distant metastasis of tumors. In recent years, 18 F-FDG PET/CT has demonstrated efficiency in staging, predicting prognosis, assessing treatment response, and determining gene mutational status in patients with CRC ( 14 17 ). MSI-H CRCs have higher intratumoral heterogeneity compared with microsatellite stability (MSS) CRCs ( 9 , 12 , 13 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Paraffin-embedded sections were used to extract deoxyribonucleic acid, and real-time fluorescent quantitative polymerase chain reaction technology was employed for amplification detection. Next-generation sequencing (NGS) was used to analyze 17 mutations in the Kirsten rat sarcoma 2 viral oncogene homolog (KRAS) gene (exons 2, 3, and 4), 13 mutations in the neuroblastoma rat sarcoma viral oncogene homolog (NRAS) gene (exons 2, 3, and 4), and 1 mutation in the v-raf murine sarcoma viral oncogene homolog B1 (BRAF) gene (exon 15: V600 E) ( 15 ).…”
Section: Methodsmentioning
confidence: 99%